The Sociological Canon, Relations between Theories and Methods, and a Latent Political Structure: Findings from a Survey of Sociology Students in Germany and Consequences for Teaching. (October 2019) - Schneickert, Christian; Lenger, Alexander; Steckermeier, Leonie C.; Rieder, Tobias
We discuss findings from a survey of sociology students in Germany and consequences for teaching. We focus on the de facto formation of a sociological canon, the relation between theories and methods, and effects of social and political characteristics on student's scientific preferences. Our findings suggest that irrespective of an agreement of the sociological professionals on a common definition of a core, a de facto canon of theories and methods exists in teaching practices. Moreover, specific relations between sociological theories and methods occur in the data. Both should be recognized in the discussion about curricula design, especially concerning teaching research methods. Finally, we discovered effects of gender and political attitude on students' preferences for theories and methods. Such differences might be associated with different motivations for studying sociology and labor market orientation. This should be considered in curricula design as well, especially at the local level of departments.